Shared neurogenetic substrates of nonplanning impulsivity and procrastination - Yuanyuan Hu; Jie Xiang; Yuening Jin; Qingchen Fan; Changshuo Wang; Yihan Wu; Dang Zheng; Yancheng Tang; Wei Li; Bowen Hu; Tingyong Feng; Yuan Zhou; et al. (Proceedings of the National Academy of Sciences, 2026)
Procrastination has a maladaptive impact on health and survival, yet it remains moderately heritable, presenting a biological paradox. Procrastination has been conceptualized as a byproduct of impulsivity, explaining its prevalence despite no discernible adaptive benefit. However, their shared neurobiological substrates have yet to be elucidated. Using a longitudinal twin cohort ( N = 154), we show that nonplanning impulsivity (NPI) during late adolescence and early adulthood is prospectively associated with procrastination in later life. This effect was independently replicated in two cross-sectional cohorts ( N = 327; N = 1,543). Twin modeling using an additive genetic and nonshared environmental (AE) framework, together with a meta-analysis of twin studies ( N = 3,656 twin pairs), revealed significant shared genetic contributions ( r g = 0.51). Beyond genetic overlap, neuroimaging meta-analysis ( NeuroSynth meta-analysis for impulsivity: k = 198 studies, 5855 loci; mini meta-analysis for procrastination: k = 5 studies, 7 independent samples, N cumulative = 893 participants), normative modeling ( N = 37,407), and seed-based d mapping (SDM) converged on the left dorsolateral prefrontal cortex (DLPFC) as the region of maximal overlap between NPI and procrastination. The transcriptional profiles of the left DLPFC and impulsivity-associated genes exhibited functional convergence on regulation of biological and cellular processes. These genes showed brain-specific expression and associations with cortical metabolism, neurodegenerative disease, and developmental expression peaks, indicating a shared molecular basis for the neurogenetic architecture of procrastination. Together, our findings delineate a cross-scale characterization of the shared neurogenetic substrates linking NPI and procrastination, offering empirical evidence that elucidates the biological origins of procrastination.